Handbook of arsenic toxicology - Flora, S. J. S. (Academic Press, an imprint of Elsevier Science, 2015)
Throughout history, arsenic has been used as an effective and lethal poison. Today, arsenic continues to present a real threat to human health all over the world, as it contaminates groundwater and food supplies. Handbook of Arsenic Toxicology presents the latest findings on arsenic, its chemistry, its sources and its acute and chronic effects on the environment and human health. The book takes readings systematically through the target organs, before detailing current preventative and counter measures. This reference enables readers to effectively assess the risks related to arsenic, and provide a comprehensive look at arsenic exposure, toxicity and toxicity prevention.- Resumé vydavatel